Trans/imagining God: Articulations of individualised spirituality among Muslim and Christian transgender men - Goh, Joseph N. (Journal for the Study of Spirituality, 2021)
Malaysian transgender people often experience suspicion, discrimination and rejection from their religious institutions. This article, written at the intersection of transgender and spirituality studies, aims to decipher the complexities of trans/imagining God, or formulations of individualised spirituality, in the lives of four transgender men. Using a constructivist grounded theory methodology, and assisted by Pargament’s notion of spiritual transformation and Tanis’s ideas on transgender spiritual traits to analyse and interpret the narratives of research participants, this article suggests that a trans/imagination of God is built on a reconfiguration of official religiosities, negotiations with romantic relationships, and a sense of obligation in terms of reaching out to others and acting ethically towards them.